Ovariectomia e treinamento resistido: influência na morfologia e angiogênese do tecido adiposo visceral de ratas - Gatto, Camila do Valle Gomes (Universidade Federal de São Carlos, 2014)
Ovariectomy in animals (surgical removal of ovaries) is a model used to mimic the menopause in women. The ovarian hormone deficiency alters the lipid profile, increases inflammation and the risk of type 2 diabetes mellitus, sarcopenia, osteopenia, obesity and cardiovascular diseases. Resistance training (RT) has been used as a non-pharmacological tool to prevent or reverse the postmenopausal effects. However, there are few studies evaluating the ovariectomy (Ovx) and RT effects on the morphology and angiogenesis of visceral adipose tissue (VAT). Thus, the aim of this study was to investigate the Ovx and RT influence at the size and adipocytes number, gene expression and VEGF-A protein levels and microvessel density in VAT of rats. Adult Sprague-Dawley rats were divided into four groups (n=6 per group): Sham-operated sedentary (Sham-Sed), ovariectomized sedentary (Sed-Ovx), Sham-operated resistance training (Sham-Tr) and ovariectomized resistance training (Ovx- Tr). During the resistance training period, the animals climbed a 1.1m vertical ladder with weights attached to their tails, which were progressively increased; the sessions were performed three times a week, with 4-9 climbs and 8-12 dynamic movements per climb with intervals of 2 minutes between climbs. Histological analysis was performed to analyze vascular micro density and morphology of VAT; gene expression and VEGF-A protein levels were analyzed by real-time PCR and ELISA, respectively. Ovx resulted in higher body weight, adipocyte hypertrophy, decreased both VEGF-A mRNA and protein and VEGF-R2 mRNA expression, and decreased the micro vascular density in the VAT of sedentary rats. However, RT was not able to prevent any changes induced by ovariectomy. The data indicated that Ovx impaired the morphology and angiogenesis of rats VAT and that RT protocol adopted did not prevent these changes. We suggest future studies performing adaptations in this resistance training program, associated or not to hypocaloric diet and treatment with estradiol.
Keywords: Ovariectomia; Treinamento resistido; Tecido adiposo; Fator de crescimento; Neovascularização; Ovariectomy; Resistance training; Visceral adipose tissue; VEGF-A and angiogenesis; CIENCIAS BIOLOGICAS::FISIOLOGIA